Implementasi Konsep Seed Pada Interior Bandar Udara Notohadinegoro Jember - Celine Destiana Siem (Intra, 2014)
Jember’s Notohadinegoro Airport is an airport located in Ajung subdistrict, Jember, East Java. The airport has not been opened and the general aviation terminal building condition does not meet the standard as the Airport Terminal. Total capacity of the airport visitors based on real data obtained from interviewing relevant parties. Was done in order to redesign the airport terminal airport terminal building standards appropriate objectives and targets as well as having a design that meets the economic value, social, political and tourism, as well as increasing the potential value of local culture and the city of Jember. The first stage of the redesign is done with the data collection and field observations to find the needs and problems of the object to be in redesigning, then the data is collected and analyzed, problem-solving solutions are then developed into a design concept that is good and right. Interior Redesign uses the concept of natural service